2004
DOI: 10.1093/jnci/djh284
|View full text |Cite
|
Sign up to set email alerts
|

Reason for Late-Stage Breast Cancer: Absence of Screening or Detection, or Breakdown in Follow-up?

Abstract: To reduce late-stage breast cancer occurrence, reaching unscreened women, including elderly, unmarried, low-income, and less educated women, should be made a top priority for screening implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 25 publications
7
108
0
2
Order By: Relevance
“…Previous studies have identified several factors associated with late stage at breast cancer diagnosis, including failure to adhere to mammography screening guidelines, age, less education, race, Hispanic ethnicity, and factors associated with decreased access to care (eg, lower income, residence in socioeconomically distressed counties, high population density, rural residence, residence in medically underserved urban areas, and lack of healthcare insurance or underinsurance). [53][54][55][56][57] Clinically, stage is used to assess prognosis, plan treatment, and evaluate outcomes. 58 The policy for the CDC's National Breast and Cervical Cancer Early Detection Program, which restricts the percentage of women aged <50 years who can be screened to 25%, 42 needs to be reviewed carefully, considering the high percentage of AI/AN women aged < 50 years (30%) who are diagnosed with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several factors associated with late stage at breast cancer diagnosis, including failure to adhere to mammography screening guidelines, age, less education, race, Hispanic ethnicity, and factors associated with decreased access to care (eg, lower income, residence in socioeconomically distressed counties, high population density, rural residence, residence in medically underserved urban areas, and lack of healthcare insurance or underinsurance). [53][54][55][56][57] Clinically, stage is used to assess prognosis, plan treatment, and evaluate outcomes. 58 The policy for the CDC's National Breast and Cervical Cancer Early Detection Program, which restricts the percentage of women aged <50 years who can be screened to 25%, 42 needs to be reviewed carefully, considering the high percentage of AI/AN women aged < 50 years (30%) who are diagnosed with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the interfaces of care and coordination among providers and institutions are critical to a successful process of cancer care. For example, studies of cancer have shown that whether people get screened accounts for a higher proportion of late-stage cancer than does the quality of the screening itself and that follow-up after an abnormal screen also is an important factor (14,15). Figure 2 shows the types of care and the triangles of communication that are established among cancer patients and their providers (16).…”
Section: The Process Of Carementioning
confidence: 99%
“…Denial may cause some patients to delay seeking treatment for suspicious symptoms or to fail to follow up on physician recommendations 15,16 . In addition, process failures in our study were more common among non-whites and Medicaid recipients, indicating a sociodemographic linkage that may be mediated by poor health literacy or practical obstacles [17][18][19][20][21][22][23][24] . For some patients, failure to report a breast lump or to adhere to a physician's recommendation may indicate a lack of understanding of the significance of the finding or the urgency of the recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…More effective outreach programs are needed to educate patients about findings suggestive of a breast abnormality, the need for regular mammography, and the urgency of adhering to followup plans. These educational interventions must be tailored to at-risk populations, targeting women whose languages, cultures, or social situations make it difficult for them to understand or implement optimal breast care 18 . A number of such interventions, including patient navigator programs and communitybased outreach efforts, have shown some success, 31,32 although further research is needed to determine which combination of initiatives is most efficacious for a given population.…”
Section: Discussionmentioning
confidence: 99%